Amyloid β deposition and glucose metabolism on the long-term progression of preclinical Alzheimer's disease. (19th February 2019) - Hatashita, Shizuo; Wakebe, Daichi
Aim: Longitudinal changes in beta amyloid (Aβ) deposition and glucose metabolism over a long-term progression of preclinical Alzheimer's disease (AD) were evaluated.Methods: 22 preclinical AD subjects with amyloid-positive scans underwent [ 11 C]-labeled Pittsburgh Compound-B (PIB) positron emission tomography (PET) and [ 18 F]-fluorodeoxyglucose (FDG) PET imaging over 6.0 ± 1.8 years. A quantitative analysis of [ 11 C]-PIB and [ 18 F]-FDG was used with a standardized uptake value ratio (SUVR) in the same regions.Results: In preclinical AD subjects, the cortical PIB SUVR was higher at baseline and increased at follow-up. 12 of the preclinical AD subjects progressed to mild cognitive impairment, six of whom had reduced glucose metabolism. The annual change in PIB SUVR was not related to that in FDG SUVR.Conclusion: Increases in Aβ deposition lead to the progression to mild cognitive impairment, but decreases in glucose metabolism do not contribute to progression. Lay abstract: Longitudinal changes in Aβ deposition and glucose metabolism were clarified over a long-term progression of preclinical AD using [ 11 C]-PIB PET and [ 18 F]-FDG PET imaging. 73% of the preclinical AD subjects progressed to mild cognitive impairment during 6 years of a long follow-up period. The increases in Aβ deposition lead to the progression to mild cognitive impairment but decreases in glucose metabolism do not contribute to progression.